2007
DOI: 10.1111/j.1398-9995.2006.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and allergies in schoolchildren of Maputo

Abstract: Asthma and allergic diseases are important public health problems in Maputo and improvement in prevention and management plans are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 25 publications
1
33
1
Order By: Relevance
“…The lowest 12-month prevalence rate of wheeze was reported in Indonesia (2.8%) during Phase III, and the highest was again reported in Costa Rica (37.6%) for the younger age group. Nigeria and Mozambique are the only African countries where ISAAC Phase I and III studies had previously been conducted for both age groups [1,15]. The 12-month prevalence rate of wheeze increased in Nigeria from 4.8% in Phase I to 5.6% in Phase III for the 6-to 7-year-old group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The lowest 12-month prevalence rate of wheeze was reported in Indonesia (2.8%) during Phase III, and the highest was again reported in Costa Rica (37.6%) for the younger age group. Nigeria and Mozambique are the only African countries where ISAAC Phase I and III studies had previously been conducted for both age groups [1,15]. The 12-month prevalence rate of wheeze increased in Nigeria from 4.8% in Phase I to 5.6% in Phase III for the 6-to 7-year-old group.…”
Section: Discussionmentioning
confidence: 97%
“…ISAAC Phase I and III studies were conducted in South Africa during 1995 and 2002 in the urban setting of Cape Town [13,14]. ISAAC Phase III studies were also conducted in urban, suburban and semi-rural areas in Maputo, Mozambique during May 2004 and in Kinshasa, the Democratic Republic of Congo [15,16]. Three of these four studies from the SADC region focused on 13-to 14-year olds and all four studies did not investigate the association between potential risk factors and asthma symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…17 Eleven surveys of the prevalence of asthma in sub-Saharan Africa were identified and are listed in Table 1. 17,20,[22][23][24][25][26][27][28][29][30] People living in rural grasslands rarely if ever suffer from allergic diseases and most of the local languages do not even have words to describe these conditions. 17,31 The prevalence of asthma varies widely between countries: Ethiopia 9.1%, Kenya 15.8%, Nigeria 13.0%, Mozambique 13.3%, and South Africa 20.3%.…”
Section: Prevalence Of Asthmamentioning
confidence: 99%
“…Exercise-induced wheeze, nocturnal cough and ever asthma were reported more frequently in children of the suburban area. These authors concluded that asthma and allergic diseases were important public health problems in Maputo and improvement in prevention and management plans were required [11].…”
Section: Prevalence Of Asthma In Southern Africamentioning
confidence: 99%
“…The ISAAC protocol was applied in 27 schools in urban, suburban and semi-rural areas in Maputo, Mozambique [11]. A total of 2630 completed questionnaires were obtained from students aged 13-14 years, and 2383 from schoolchildren aged 6-7 years.…”
Section: Prevalence Of Asthma In Southern Africamentioning
confidence: 99%